Millimeter-wave beam scattering by edge-plasma density fluctuations in TCV. (7th November 2018) - Chellaï, O; Alberti, S; Baquero-Ruiz, M; Furno, I; Goodman, T; Labit, B; Maj, O; Ricci, P; Riva, F; Guidi, L; Poli, E
Abstract: In magnetically confined fusion devices, the use of millimeter waves (mmw) at the electron cyclotron (EC) frequencies ranges from plasma diagnostics to plasma heating, current drive and core confinement preservation. For large tokamaks such as ITER, numerical simulations and analytical estimates suggest that plasma edge turbulence could significantly broaden the EC-beam, possibly preventing tearing modes stabilization at the designed power levels. We report measurements of mmw-beam scattering by plasma turbulence in the TCV tokamak. A mmw-Gaussian beam is injected from the top of the device and the transmitted power is measured at the bottom. We show that the measured plasma density fluctuations in the upper part of the scrape-off layer (SOL) are the cause of fluctuations of the transmitted mmw-power. A full-wave model based on COMSOL multiphysics is presented and compared against the wave-kinetic-equation solver WKBeam in a TCV case. Using the SOL turbulence simulations from the GBS code, comparison between the scattering effect on the mmw-beam with both the full-wave simulations and the experiments are ongoing. We also present experimental observations of rapid changes in the transmitted power caused by ELMs in ELMy H-mode plasma.